Proceedings of the SIGCHI-NZ Symposium on Computer-Human Interaction - CHINZ '02 2002
DOI: 10.1145/2181216.2181220
|View full text |Cite
|
Sign up to set email alerts
|

Analysing mouse and pen flick gestures

Abstract: Gesture based interfaces promise to increase the efficiency of user input, particularly in mobile computing where standard input devices such as the mouse and keyboard are impractical. This paper describes an investigation into the low-level physical properties of linear 'flick' gestures that users create using mouse and pen input devices. The study was motivated by our need to determine sensible constraints on values such as the magnitude, timing, and angular accuracy of gestures for a marking-menu implementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Yet, hands impose kinematic constraints that make it easier to draw strokes in some directions and more difficult others. Prior work on marking menus has studied the speed and accuracy with which users can draw one or more directional strokes in the context of stylus and mouse-based marking menus [Kurtenbach and Buxton 1993;Moyle and Cockburn 2002;Zhao et al 2006;Zhao and Balakrishnan 2004]. Working with two hands using touch-based devices is likely to impose a different set of constraints on the hand motions.…”
Section: User Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, hands impose kinematic constraints that make it easier to draw strokes in some directions and more difficult others. Prior work on marking menus has studied the speed and accuracy with which users can draw one or more directional strokes in the context of stylus and mouse-based marking menus [Kurtenbach and Buxton 1993;Moyle and Cockburn 2002;Zhao et al 2006;Zhao and Balakrishnan 2004]. Working with two hands using touch-based devices is likely to impose a different set of constraints on the hand motions.…”
Section: User Studymentioning
confidence: 99%
“…Strokes are scale-independent and users can draw them in-place and in an eyes-free manner. Extensive studies have shown that users can draw directional strokes quickly and accurately [Kurtenbach and Buxton 1993;Moyle and Cockburn 2002;Zhao et al 2006]. Marking menus also facilitate novice to expert transition.…”
Section: Introductionmentioning
confidence: 99%
“…Adding this online correction to flicking gestures significantly improved their accuracy. Another study by Moyle and Cockburn [13] compared linear mouse and pen flicking gestures, and found mouse flicking to be more accurate. They also showed that downwards flicking gestures where conducted more slowly than those pointing upwards.…”
Section: Related Workmentioning
confidence: 99%
“…Since the touch screens have similar behavior as the mouse, mouse gesture recognizer [Moyle and Cockburn 2002;Lombardi and Porta 2007;Buckland 2002] could be adapted in order to be used by touch screen devices. But this could be very hard since they are not adapted for the low processing power and memory constraints of such devices.…”
Section: Touch Devicesmentioning
confidence: 99%